Novel Contributions to the System of Fractional Hamiltonian Equations - Tayeb Mahrouz; Abdelaziz Mennouni; Abdelkader Moumen; Tariq Alraqad (Mathematics, 2023)
This work aims to analyze a new system of two fractional Hamiltonian equations. We propose an effective method for transforming the established model into a system of two distinct equations. Two functionals that are connected to the converted system of fractional Hamiltonian systems are introduced together with a new space, and it is demonstrated that these functionals are bounded below on this space. The hypotheses presented here differ from those provided in the literature.